Axonal Injury with Persistent Neuropathy following Popliteal Nerve Block for Cheilectomy Surgery - Y. A. M. Kuijpers; J. M. Setz; K. Khemlani-Houthoff (Case Reports in Anesthesiology)
Peripheral nerve blocks are often used for foot and ankle surgery. The occurrence of persistent neurological symptoms thereafter is very rare. Preventive strategies pose no guarantee and uncovering true etiology is often complicated. We discuss a case in which a young, healthy patient developed nerve damage after an uneventful popliteal block and cheilectomy. Nerve conduction studies revealed axonal injury in the distribution area of the sciatic nerve. The neurological symptoms persisted for more than 12 months, emotionally affecting the patient greatly. Patients will primarily report to the orthopedic surgeon, for whom cooperation with anaesthesia and neurology is of importance. Anesthetic involvement probably improves patient satisfaction during complication management.